Population Age Structure and the Budget Deficit - Chen, Derek H. C. (World Bank, Washington, D.C., 2013)
The author focuses on the effects of age structure changes on the size of budget deficits of national governments. More specifically, he determines whether differences in age structure can account for the observed differences in budget deficits across countries as well as across time. By way of an extension of the untested theory of negative bequest motives advocated by Cukierman and Meltzer (1989), the author argues that the commonly accepted notion that population aging tends to increase the budget deficits of economies is theoretically consistent. However, preliminary results from country and time fixed-effects panel regressions, estimated from 1975 to 1992 over 55 industrial and developing countries, indicate statistical evidence for this postulation is present only in the developing countries but not in the industrial countries.